Advantages of Seeding Annual and Perennial Cover Crops Between Peach Rows - Ciacci, María Belén (2022)
Soil degradation constitutes a limiting factor for fruit production in the “Oasis Sur” region of Mendoza (Argentina). Conversely, seeding cover crops is an important practice to reduce the production risks. The objective of this research was to quantify the effects of different cover crops seeded between the peach trees rows on the soil properties and water potential and mineral composition of the leaves of peach. The study was carried out in Mendoza, during two cover crops growing cycles. Treatments were control (CT), lucerne cover crop (LT), and a mixture of common vetch and oat (VOT). The experimental design was a randomized complete three blocks with three replications per treatment. In LT, biomass production was three-fold higher than in VOT and significantly increased the coarse fraction of the soil organic carbon. In LT and VOT, the soil showed a 16% of increase in the volumetric moisture content compared to CT. Both cover crops improved the soil easily available water content, total porosity, and air-filled porosity. Peach trees showed better water status in LT and higher leaves nitrogen content in VOT. The practice of seeding cover crops between the rows of peach trees is a very useful alternative for semi-arid areas since they improve the efficiency in the use of water and nutrients by fruit trees.